2022
DOI: 10.3389/fsufs.2022.984391
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol nanoemulsion inactivates Listeria monocytogenes, Salmonella Enteritidis, and Escherichia coli O157:H7 on cantaloupes without affecting rind color

Abstract: Listeria monocytogenes, Salmonella Enteritidis, and Escherichia coli O157:H7 are the major foodborne pathogens that have been implicated in outbreaks related to consumption of contaminated cantaloupes. Current chlorine-based decontamination strategies are not completely effective for inactivating the aforementioned pathogens on cantaloupes, especially in the presence of organic matter. This study investigated the efficacy of eugenol nanoemulsion (EGNE) wash treatments in inactivating L. monocytogenes, Salmonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
0
0
Order By: Relevance
“…Encapsulation of phytochemicals using emulsifiers enhances their water dispersibility, resistance to environmental conditions, and antimicrobial potency (Ray et al, 2016;Ferreira and Nunes, 2019). Several researchers (Moghimi et al, 2016;Rinaldi et al, 2021) including our lab (Balasubramanian et al, 2022;Allen et al, 2023) have reported that antibacterial potency of volatile essential oils is augmented in nanoemulsion form as compared to its corresponding oil form against various food borne pathogens. In this study, we used gum Arabic and lecithin which are food-grade emulsifiers and are widely employed in the food industry (Patel and Goyal, 2015;Sethuraman and Rajendran, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encapsulation of phytochemicals using emulsifiers enhances their water dispersibility, resistance to environmental conditions, and antimicrobial potency (Ray et al, 2016;Ferreira and Nunes, 2019). Several researchers (Moghimi et al, 2016;Rinaldi et al, 2021) including our lab (Balasubramanian et al, 2022;Allen et al, 2023) have reported that antibacterial potency of volatile essential oils is augmented in nanoemulsion form as compared to its corresponding oil form against various food borne pathogens. In this study, we used gum Arabic and lecithin which are food-grade emulsifiers and are widely employed in the food industry (Patel and Goyal, 2015;Sethuraman and Rajendran, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The sonication process involved a cycle of 10 s of operation followed by 5 s of rest, with an amplitude of 60 Watts. According to Balasubramanian et al (2022), the nanoemulsion's composition consisted of 1.25% eugenol, 0.5% gum Arabic, 0.5% lecithin, and 16.66% ethanol.…”
Section: Preparation Of Eugenol Nanoemulsionmentioning
confidence: 99%